Hardfacing of AISI 1020 Steel by Arc Welding in Comparison with TIG Welding Processes (Journal of Scientific Research, 2012)
Hardfacing techniques are used for enhancing the life of various machine parts by rebuilding the worn out or eroded or corroded areas in them. In this paper, an attempt has been made to determine the better welding process to hardface AISI 1020 steel based on study of wear and other factors. Two types of welding processes - Arc welding and tungsten inert gas welding (TIG) have been compared. The study revealed that the specimens prepared using TIG welding process yielded better wear properties compared to the specimen prepared using Arc welding process till 1.256 m/s sliding velocity. Also it was observed that the Arc welding process yielded better wear properties for sliding velocities above 1.571 m/s. An attempt was made to study the reasons for getting the said results.© 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i1.11899        J. Sci. Res. 5 (1), 119-126 (2013)